2011
DOI: 10.1021/ac1027462
|View full text |Cite
|
Sign up to set email alerts
|

Mortar Radiocarbon Dating: Preliminary Accuracy Evaluation of a Novel Methodology

Abstract: Mortars represent a class of building and art materials that are widespread at archeological sites from the Neolithic period on. After about 50 years of experimentation, the possibility to evaluate their absolute chronology by means of radiocarbon ((14)C) remains still uncertain. With the use of a simplified mortar production process in the laboratory environment, this study shows the overall feasibility of a novel physical pretreatment for the isolation of the atmospheric (14)CO(2) (i.e., binder) signal absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 34 publications
0
61
0
Order By: Relevance
“…The initial CryoSoniC procedure (Marzaioli et al 2011), which was developed at CIRCE (Centre for Isotopic Research on Cultural and Environmental heritage), was modified after …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial CryoSoniC procedure (Marzaioli et al 2011), which was developed at CIRCE (Centre for Isotopic Research on Cultural and Environmental heritage), was modified after …”
Section: Methodsmentioning
confidence: 99%
“…Thanks to the Mortar Dating Project (www.mortardating. com) the 14 C dating of mortar became more popular with other laboratories, and new or modified protocols of mortar preparation have appeared Marzaioli et al 2011;Hajdas et al 2012;Hodgins et al 2011;Marzaioli et al 2013;Michalska et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…The unburnt problem and its contribution to bias in age determination has been studied by Marzaioli et al (2011).…”
Section: Resultsmentioning
confidence: 99%
“…The principle of 14 C dating is that binder carbonates absorb carbon dioxide from the atmosphere, thus making mortars potentially suitable for 14 C dating. The method of 14 C dating mortar has been applied since the 1960s, but frequently the isotopic age and the expected historic age show contradictory results (Labeyrie and Delibrias 1964;Stuiver and Smith 1965;Baxter and Walton 1970;Van Strydonck et al 1983, 1986, 1992Ambers 1987;Heinemeier et al 1997aHeinemeier et al , 2010Hiekkanen 1998;Hale et al 2003;Nawrocka et al 2005Nawrocka et al , 2007Nawrocka et al , 2009Lindroos et al 2007;Marzaioli et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…However, recently studies have shown that accurate sample processing allow a significant reduction of these error sources (Sonninen & Junger, 2001, Marzaioli et al, 2011 and see also the contribution of Ortega and its colleagues in this book) and moreover adoption of a special sampling procedure based on the careful selection of lumps of incompletely mixed lime, provides an interesting alternative that avoids problems associated with contamination.…”
Section: Radiometric Dating 22mentioning
confidence: 99%